KOHESI DAN KOHERENSI PADA SKRIPSI MAHASISWA PENDIDIKAN BAHASA INGGRIS - , CUT IRNA LIYANA, Prof. Dr. Soepomo Poedjosoedarmo ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study is entitled Cohesion and Coherence in English Education Studentsâ Thesis. The aim of this study is to describe the cohesion and coherence as wholeness aspect of discourse in English Education studentsâ thesis. This study is a qualitative research. The data sources in this study are the thesis of three students that were obtained by purposive sampling. Furthermore, analysis of the data was done by identifying and classifying the data that related to cohesion, based on the theory of Halliday and Hasan (1976), and related to coherence, based on the theory of Oshima and Hogue (1991). From analysis, it was found four things related to cohesion and coherence. First, the use of grammatical cohesion devices in thesis, which consists of reference, substitution, ellipsis, and conjunction